SANKSI HUKUM TERHADAP PELANGGARAN LALU LINTAS DAN ANGKUTAN JALAN - Sunarto, Sunarto; Prawesthi, Wahyu; Borman, M. Syahrul (Gapenas Publisher, 2025)
This normative juridical study analyzes legal sanctions for road traffic and transport violations as a vital instrument for achieving public order and safety. The research examines the legal foundation, forms of violations, and the effectiveness of sanctions regulated in Law Number 22 of 2009 on Road Traffic and Transport (LLAJ Law). The analysis indicates that violations are a multidimensional issue caused not only by individual factors but also by inconsistent law enforcement and social culture. The study asserts that sanctions, whether in the form of administrative fines or imprisonment, serve to provide a deterrent effect, reduce accident rates, and strengthen legal certainty. Although the regulatory framework exists, its implementation on the ground still faces challenges such as collusion and limited resources. As a recommendation, this study proposes a transformation in law enforcement through digitalization (electronic traffic ticketing/ETLE system), enhanced transparency, and the implementation of a demerit point system for driver's licenses. These measures aim to build a sustainable culture of traffic discipline and increase public trust in the justice system